The Experience and Perceived Consequences of the 2016 Fort McMurray Fires and Evacuation - Thériault, Laura; Belleville, Geneviève; Ouellet, Marie-Christine; Morin, Charles M. (Frontiers in Public Health, 2021)
Few studies have examined the scope of the subjective experience during and after a natural disaster. This qualitative study explored the perceptions of persons affected by the wildfires and evacuation of Fort McMurray in 2016. The objectives were to document (1) the experience of the evacuation, and (2) the biopsychosocial consequences of the wildfires as perceived by evacuees from Fort McMurray 3 months and 3 years after evacuation. This study included two data collections, one from 393 evacuees 3 months after evacuation using an online questionnaire, and the other from 31 participants (among those who participated in the 3-month evaluation) interviewed by telephone 3 years after evacuation. Eight themes describing the evacuation experience emerged from the qualitative analysis: the preparation for evacuation, the perceived traumatic nature of the evacuation, problems encountered while on the move, assistance received and provided, vulnerability conditions, presence of physical discomfort, relocation and no problem/no response. Seven categories of negative consequences emerged: material and financial loss, emotional/mental health disorders, cognitive impairments, behavioral changes, spiritual/existential reflections, social alterations, and physical conditions. Four categories of positive consequences emerged: posttraumatic growth, resilience/absence of consequences, altruism and community cohesion. This study showed a wide range of perceived consequences of fires and evacuations by Fort McMurray residents. The results highlight the importance of tailoring responses to the needs of evacuees and providing assistance to victims over a long period of time.